Protestantism in Korea during the Japanese regime (1910-1945) - Choi, Yeon-Kyu ([n.p.] South East Asia Graduate School of Theology, 1993)
Not counting the attempts earlier in the century to circulate Scripture portions, Protestant beginnings in Korea may be traced to about 1872 through the work of Scottish United Presbyterian missionaries in Manchuria. The first Protestant missionaries specifically assigned to Korea began arriving in 1885. Within a few years, Presbyterian and Methodist mission churches were established.
This period in the late 19th century was one of transformation and reform for Korea, as a result of contact with the modern world
In partial fulfillment of the requirements for the degree of Master of Theology South East Asia (S.E.A.)
A thesis presented to the faculty of the South East Asia Graduate School of Theology
Thesis (M.Theo)- South East Asia